Basic Standard Procedure of Abdominal Hysterectomy: Part 1 - Hiramatsu, Yuji (The Surgery Journal, 2019)
Total abdominal hysterectomy (TAH) is commonly referred to as extrafascial hysterectomy. This article explains the basic surgical procedure of TAH as taught to residents. TAH is an operation to remove the uterus with the outer wall of the uterus, and is a fundamental operation that gynecologists must master. Possible complications during TAH include ureteral injury, intestinal damage, and bladder injury. To avoid operative complications, it is important to follow the correct release layer procedure and ensure that “the uterus has been naturally removed.”The two most important points of the authors' method to avoid complications are as follows: (1) cut sequentially from the ligament away from the ureter which moves the ureter further away from the cervix with each transection stage; (2) cut the parametrial tissue along the circumference of the cervix in the next three steps:First step: clamping and cutting the uterine artery and upper part of the cardinal ligament; second step: clamping and cutting the sacrouterine ligament and the posterior half of the cardinal ligament; third step: clamping and cutting the vesicouterine ligament and anterior half of the cardinal ligament.
Keywords: abdominal hysterectomy; basic standard procedure; uterine fibroid